A besta não é invencível: uma crítica à religião do mercado - Santos, Mônica de Souza (2011)
The present work is an analysis of the present state of Neoliberalism seen in the light of Apocalypse Thirteen. In the first chapter, historical and sociological elements are sought, so that they might elucidate the relationship between capitalism and religion. It includes a summary of the consolidation of liberal thought following the ideas of Adam Smith, the welfare state of Keynes, and the theories of Hayek and Neoliberalism s official implantation in the so called Washington Consensus. The chapter addresses the connection between religion and capitalism according to the theories of Max Weber, Walter Benjamin and Adam Smith. The second chapter studies the historical roots and characteristics of Apocalyptic Literature. The aim is to identify the movement behind this literature; that is, one of prophetic resistance against a power that oppresses and excludes people. Thus, the apocalyptic books must be read as a contestation and denunciation of the tyranny of the Roman Empire which imposed itself as a god. The third chapter is dedicated to the interpretation of chapter thirteen of the Apocalypse, in which the two beasts are described as receiving their power from the dragon. These are understood as keys that help us unmask the false marketing of religion, built and justified upon neoliberal theories. Finally, the chapter concludes with the reconstruction of hope today, based on the real experience of confronting Neoliberalism as the ultimate model.